Associations Between Sleep Quality and 10-Year Cardiovascular Disease Risk Among Female Nurses in Hong Kong: A Cross-sectional Study. Issue 3 (24th May 2022) - Yan, Lin Jia; Xie, Yao Jie
Abstract : Background: Sleep problems are common among nurses compared with the general population. Poor sleep quality increases the risk of developing cardiovascular disease (CVD). The relationship between sleep quality and CVD risk has not been previously investigated among Hong Kong female nurses. Objective: The authors of this study explored the association between sleep quality and CVD risk among Hong Kong female nurses. Methods: Data were collected from the Hong Kong Women's Health Study cross-sectional survey between 2019 and 2020. Questionnaires were sent to female nurses (≥aged 30 years). Ten-year CVD risk was measured using the Framingham 10-year risk score, and the Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality. Relationships were evaluated using adjusted multiple linear regression and binary logistic regression. Results: In 1344 respondents, the mean age was 46.12 ± 10.47 years, average PSQI score was 6.02 (3.35), and 52.4% reported poor sleeping quality (global PSQI score > 5). The mean 10-year CVD risk was 3.6% (3.3%). The 10-year CVD risk was significantly associated with sleep disturbance (β = 0.006) and daytime dysfunction (β = −0.002) (both P s < .01). Participants who reported sleep disturbance had a higher CVD risk (odds ratio, 1.82; 95% confidence interval, 1.04–3.18). High daytime dysfunction decreased CVD risk (odds ratio, 0.63; 95% confidence interval, 0.46–0.85). Subgroup analysis showed stronger associations between sleep quality and Framingham 10-year risk score among those unemployed, undergoing postmenopause, or with a family history of CVDs. Conclusions: Sleep disturbance and daytime dysfunction were associated with the 10-year CVD risk among Hong Kong female nurses. Nurses who were unemployed, were undergoing postmenopause, or with a family history of CVD were those with the highest risk.